2021
DOI: 10.1039/d1dt00269d
|View full text |Cite
|
Sign up to set email alerts
|

Vapochromic behaviour of a nickel(ii)-quinonoid complex with dimensional changes between 1D and higher

Abstract: The nickel(II)-chloranilato complex {Ni(ca)(VM)2}n (H2ca = chloranilic acid, VM = coordinated vapour molecules, such as water) shows reversible vapochromism upon exposure to various vapours and subsequent drying by heating. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…26 In addition to the classical thermal-induced SCO, [27][28][29] a peculiar magnetic switch known as coordination-induced spin-state switching (CISSS) is bistable at room temperature in homogeneous solution [30][31][32][33][34] or solid state. [35][36][37][38][39] It is of general knowledge that the spin state of nickel(II) complexes depends on the coordination number and geometry, thus the square planar Ni-center diamagnetic low-spin state can be switched to a high spin state (S = 0 → S = 1) by controlling axial ligation to a square pyramidal or octahedral configuration. In this regard, Ni II -based CISSS phenomenon provides a promising strategy for the control of the spin-state at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition to the classical thermal-induced SCO, [27][28][29] a peculiar magnetic switch known as coordination-induced spin-state switching (CISSS) is bistable at room temperature in homogeneous solution [30][31][32][33][34] or solid state. [35][36][37][38][39] It is of general knowledge that the spin state of nickel(II) complexes depends on the coordination number and geometry, thus the square planar Ni-center diamagnetic low-spin state can be switched to a high spin state (S = 0 → S = 1) by controlling axial ligation to a square pyramidal or octahedral configuration. In this regard, Ni II -based CISSS phenomenon provides a promising strategy for the control of the spin-state at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is for this reason that a large number of porphyrin derivatives, are selected to investigate the Ni II based CISSS behavior, advancing this field for application into switchable contrast agents for magnetic resonance imaging (MRI) 40 and molecular spintronics. 41,42 Beyond the range of Ni II -porphyrin complexes, considerable attention is also concentrated on expanding the CISSS systems based on quinonoid, 35,38 chlorins, 43 salicylidenepropylene iminate, 34 paddle wheel 37 and phenazine-based Schiff base like ligands. 44 With the above in mind, we recently reported that a solidstate CISSS phenomenon on Ni-salicylisonicotinohydrazide system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 1D structure of an analogous Ni(II)−quinonoid complex [Ni(ca)-(OH 2 ) 2 ] n (ca = chloranilate) changes to a higher dimensional one upon desorption of water molecules by heat (see Scheme 1B), which changes its color from green to dark brown. 9 Intermolecular interactions in the crystalline phase may be an important aspect in understanding the characteristic features of soft crystals. Thus, knowledge of the crystal structure of 1P is key to discussing the mechanistic aspects of vapochromism in the Ni(II)−quinonoid complex.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an ethyl-substituted analog of 1P (denoted 2P ), which does not absorb methanol molecules, shows an absorption spectrum that is similar to that of 1P but a qualitatively different PXRD pattern. In addition, the 1D structure of an analogous Ni­(II)–quinonoid complex [Ni­(ca)­(OH 2 ) 2 ] n (ca = chloranilate) changes to a higher dimensional one upon desorption of water molecules by heat (see Scheme B), which changes its color from green to dark brown . Intermolecular interactions in the crystalline phase may be an important aspect in understanding the characteristic features of soft crystals.…”
Section: Introductionmentioning
confidence: 99%